Analisis pengaruh kebijakan pemerintah dalam penundaan pembayaran hutang dimasa pandemic diperusahaan makanan dan minuman - H. Adam Afiezan; Muhammad Reza; Syvania Eyeline; Morita Malau (Politeknik Ganesha Medan, 2022)
Benefit is one of the primary objectives of each and every business substance. Without procuring a benefit, the organization can't satisfy its different goals, specifically ceaseless development (going concern) and the obligation to satisfy commitments in paying the organization's obligations. This commitment is a benchmark for the public authority in making a strategy. This study means to exactly look at government approaches in deferring obligation installments during the pandemic on benefit, liquidity, obligation strategy and free income in the food and refreshment area recorded on idx. This study utilizes a quantitative exploration approach that underlines a causal relationship that looks at government strategy in deferring obligation installments as an autonomous variable on benefit, liquidity, obligation strategy and free income as the reliant variable. The information assortment process in this study utilizes optional information sources as monetary reports for organizations in the food and drink area for the 2018-2020 period. The technique utilized for inspecting is purppose testing. The outcomes showed that there was no massive impact between ROA on Government Strategy. In the mean time, Liquidity, Free Income and DER affect Government Strategy